Cultivating mathematical mindset via online video interventions: a mixed-methods investigation in Chinese higher education - Xu, Xiaoyu; Broadbent, Jaclyn; Zhang, Qiaoping (Frontiers in Psychology, 2025)
Freshmen often encounter significant challenges in adapting to the complexity of university-level mathematics and independent learning. These challenges necessitate the development of strong self-regulated learning (SRL) skills to successfully navigate the demands of higher education. Building on mindset theory, this study explores how mathematical mindset-oriented interventions can support freshmen’s mathematics learning during their transition to higher education mathematics, particularly in an online setting. This mixed-methods study involved 306 freshmen, who participated in an online calculus tutorial program, with 118 engaged in the mindset intervention and 188 serving as controls. The intervention significantly altered the students’ perceptions of mathematics and improved their SRL strategies. Quantitative data were analyzed using descriptive statistics, ANOVA, t-tests, and Structural Equation Modeling to examine the relationships between mathematical mindset, SRL, and academic achievement. Qualitative data from semi-structured interviews with 18 students were thematically analyzed to provide deeper insights into students’ experiences and mindset development. Students with a mathematical mindset demonstrated enhanced SRL strategies and superior mathematical achievement. However, the fact that some students with a fixed mindset also achieved high levels of mathematical success points to the intervention’s complex influence on academic confidence and achievement. These findings highlight the need for ongoing research into the mathematical growth mindset at the tertiary level and for adapting educational strategies to the changing dynamics of online education and diverse cultural backgrounds.